Effects of Vertical Irregularity (Upper Level) of 5-Storey Laboratory Steel Tower Using Modal Analysis - Rosle, Nurshahirah; Kamarudin, Ahmad Fahmy (Recent Trends in Civil Engineering and Built Environment, 2021)
Buildings with vertical irregularity at upper level often amaze people with its esthetical design and unique appearance. The increasement of population and urbanization force the engineers to come out with safe and unique building designs occupied with its multi-functional spaces uses. However, irregular building design build up from complex dynamic behavior compared to regular buildings design. Therefore, this study was conducted to determine the effects of vertical irregularity at upper level of 5-storey laboratory steel tower using modal analysis via STAAD.Pro software. The dynamic characteristics of steel tower was investigated in terms of predominant frequencies and mode shape. The results of bare frame (control tower) were compared to previous laboratory testing for verification purpose before implement the four cases of irregularity on the steel tower. The first three predominant frequencies of bare frame and irregular cases were arranged according to their modes. The frequencies of bare frame were f1 and f2 = 5.55Hz, and f3 = 7.21Hz with percentage difference less than 10% from previous study. There were 3 type of mode shapes experienced by the steel tower which were translational for mode 1 and 2, and torsional for mode 3. Hence, vertical irregularities could be considered a risk for a building compared to regular building design.